METODE TAKHRIJ HADIS DALAM VERIFIKASI KEAUTENTIKAN HADIS NABI - Sofiana Sholikah; Alvin Haidar; Ahmad Syaiful Ghozi; Nur Efendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Takhrij method is used to trace the original source of a hadith and verify its authenticity. The aim of this study is to explain the meaning and use of takhrij hadith, the takhrij method in hadith books, and the verification of the quality of hadith sanad and matan. The study employed a literature review approach, examining various hadith books and related scientific sources on takhrij. The results of this study show that the takhrij process can be carried out using several reference books such as Al-Jami’ al-Shaghir, Al-Mu’jam al-Mufahras li Alfazh al-Hadith, Musnad Ahmad ibn Hanbal and Miftah Kunuz as-Sunnah, which have different search systems. Sanad verification is carried out through the analysis of ittisal al-sanad, ‘adl, dabit, syaz, and ‘illat to ensure the validity of the hadith’s transmission chain. Verification of the matan is performed by evaluating the consistency of the hadith with the Qur'an, stronger hadiths, common sense, historical facts, and the linguistic characteristics of the Prophet Muhammad. Therefore, takhrij plays a vital role in maintaining the authenticity of hadiths and the purity of Islamic teachings.